IMPLEMENTASI MODEL PRESTASI UNTUK MENINGKATKAN MOTIVASI BELAJAR DAN KOLABORASI PADA SISWA KELAS V SDN 6 TANJUNG - Muhammad Bagoes Pribadi; Noorhapizah; Akhmad Riandy Agusta; Tika Puspita Widya Rini (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is motivated by the lack of learning motivation and collaboration skills, which leads to a lack of variety in learning models and student engagement. This study aims to describe learning motivation and analyze collaboration skills through the application of the PRESTASI model. The method used is Classroom Action Research (CAR) in three meetings, with 12 fifth-grade students of SDN 6 Tanjung in the second semester of the 2024/2025 academic year as subjects. The approach used is qualitative and quantitative, with data obtained through observation, interviews, and tests. The results show that student learning motivation increased from